Coplanar UHF RFID tag antenna with U-shaped inductively coupled feed for metallic applications - Al Khanjar, Karrar Naji Salman; Ismail, Alyani; Raja Abdullah, Raja Syamsul Azmir; Saeedi, Tale (Public Library of Science, 2017)
In this paper, we present a novel compact, coplanar, tag antenna design for metallic objects. Electrically small antenna has designed for a UHF RFID (860–960 MHz) based on a proximity-coupled feed through. Furthermore, two symmetrical Via-loaded coplanar grounds fed by a U-shaped inductively coupled feed through an embedded transmission line. This configuration results in an antenna with dimensions of 31 × 19.5 × 3.065 mm3 at 915 MHz, and the total gain for the antenna is 0.12 dBi. The Via-loaded coplanar and U-shaped inductively coupled feeds allow the antenna to provide flexible tuning in terms of antenna impedance. In addition, a figure of merit is applied for the proposed tag antenna, and the results are presented. The read range is measured to be 4.2 m, which is very close to simulated values. This antenna measurement shows very good agreement with simulations.